Da construção do currículo à aprendizagem significativa: a prática docente de geografia na educação de jovens e adultos - SOUZA, Camila Vianna de (Universidade Federal do Pará, 2021)
The work aims to present the reality of the contemporary educational context of Youth and Adult Education (EJA) to understand students as subjects and objects in the teaching-learning process, that is, the reality, the places of experiences, their routines and their references cultural. In this way, teachers can organize and plan the curriculum so that the construction of knowledge has meaning and meaning in the lives of students. The research also presents an analysis of the curricular structure of the Geography discipline in the Youth and Adult Education (EJA) modality in the municipality of Duque de Caxias, RJ. The discussions in this article point to the need to reconfigure the school curriculum of that municipality and the relevance of working with the contents based on the students' socio-spatial practices, as this way students can (re) know themselves within their reality, enabling meaningful learning, making the student the subject of the didactic-pedagogical process in Geography.